Comparative Evaluation of the Antimicrobial Efficacy of Sodium Hypochlorite, Silver Nanoparticles, and Zinc Nanoparticles against Candidal Biofilm: An In Vitro Study - Varsha Ravi; Sandya Kini; Neetha Shenoy; Krishnaraj Somayaji; Padmaja Shenoy (Engineering Proceedings)
The aim of the present investigation was to evaluate and compare the antifungal activity of sodium hypochlorite (NaOCl), silver nanoparticles (Ag-NP), and zinc nanoparticles (ZnO-NP) against candidal biofilms. Twenty-two single-rooted premolars were decoronated to a root length of 12 mm. Shaping of the canals was done with ProTaper size F2 files. The specimens were inserted into vials containing 2 mL of the Sabouraud broth and then incubated for 14 days. From n = 22, one sample was subject to SEM evaluation, and from one more sample, dentinal shavings were taken on a Sabouraud dextrose agar plate to confirm the presence of candidal biofilms. The remaining 20 samples were divided (n = 5) and irrigated as follows. Group 1: saline; Group 2: 5.25% NaOCl; Group 3: 0.02% Ag-NPs; Group 4: 0.02% Zn-NPs. The CFUs (colony forming units) were determined per group. SEM imaging of one sample per group was undertaken to correlate the microbiological results. Statistical analysis was conducted using Kruskal–Wallis, with p < 0.05 kept as the significant level. NaOCl reduced the colony counts to a maximum, which was of statistical significance, followed by Ag-NP and Zn-NP. Saline showed the least antimicrobial efficacy. NaOCl was the most effective irrigant against candidal biofilms. Ag-NPs and ZnO-NPs reduced the fungal load but failed to eradicate the biofilm completely.